PELATIHAN PEMANFAATAN QUIZIZZ DALAM PEMBUATAN MEDIA PEMBELAJARAN DI SMK NEGERI 1 RAMBAH SAMO - Wahyudi, Sri; Chandra, Detri Amelia; Muslim, Muslim; Santosa, Firman; Yunita, Nova (Smart Education, 2025)
Abstract: The Industrial Revolution 4.0 era requires the world of education to adapt to technological developments, including in the learning process. Interactive learning media is one of the innovative solutions to increase student participation and motivation in learning. This article discusses the results of training activities to create interactive learning media based on the Quizizz application carried out at SMK Negeri 1 Rambah Samo by a team of lecturers from Rokania University. This training aims to improve teacher competence in designing and implementing digital teaching media that are interesting, effective, and in accordance with student characteristics. The implementation method uses a participatory approach and direct practice, including an introduction to the Quizizz feature, compiling questions, and learning simulations. The results of the activity show that teachers are able to use the application independently and produce Quizizz-based learning materials that are ready to be used in class. In addition, this training also produces outputs in the form of technical guide modules and scientific articles. This activity has a positive impact in encouraging a more interactive and adaptive learning transformation to technology. Keyword: Interactive learning, Quizizz, Educational technology, Teacher training, Digital media. Abstrak: Era Revolusi Industri 4.0 menuntut dunia pendidikan untuk beradaptasi dengan perkembangan teknologi, termasuk dalam proses pembelajaran. Media pembelajaran interaktif menjadi salah satu solusi inovatif untuk meningkatkan partisipasi dan motivasi siswa dalam belajar. Artikel ini membahas hasil kegiatan pelatihan pembuatan media pembelajaran interaktif berbasis aplikasi Quizizz yang dilaksanakan di SMK Negeri 1 Rambah Samo oleh tim dosen Universitas Rokania. Pelatihan ini bertujuan untuk meningkatkan kompetensi guru dalam mendesain dan mengimplementasikan media ajar digital yang menarik, efektif, dan sesuai dengan karakteristik siswa. Metode pelaksanaan menggunakan pendekatan partisipatif dan praktik langsung, mencakup pengenalan fitur Quizizz, penyusunan soal, serta simulasi pembelajaran. Hasil kegiatan menunjukkan bahwa guru mampu menggunakan aplikasi secara mandiri dan menghasilkan materi pembelajaran berbasis Quizizz yang siap digunakan di kelas. Selain itu, pelatihan ini juga menghasilkan luaran berupa modul panduan teknis dan artikel ilmiah. Kegiatan ini memberikan dampak positif dalam mendorong transformasi pembelajaran yang lebih interaktif dan adaptif terhadap teknologi. Kata kunci: Pembelajaran interaktif, Quizizz, Teknologi pendidikan, Pelatihan guru, Media digital.